Agir auprès des femmes immigrantes: analyse des représentations identitaires professionnelles des conseillers d’orientation - Cardu, Hélène; Sanschagrin, Mélanie (Canadian Journal of Counselling and Psychotherapy, 2007)
We present the results of research on guidance counsellors’ perception of their professional skills in work with immigrant women in the metropolitan Quebec region, focussing in particular on their knowledge of the social and occupational context in which immigrant women are integrated and the practices involved. Immigrant women landing in Quebec City, a monocultural city, experience cultural uprooting accompanied by compromises in the construction of a new occupational image. The set of intercultural skills developed by occupational guidance practitioners (N = 20) are discussed from an ego-ecological perspective (Zavalloni, 1990; Zavalloni & Louis-Guérin, 1984).